Developing a use-inspired school and community-based 6th through 12th-grade research and invention ecosystem leading to STEM careers: an ethnographic study of the Science Coach Program - Melinda Z. Kalainoff; Fatiha Bazouche; Stephanie R. Couch; Jill M. Ott (Frontiers in Education)
This study responds to the need for educational offerings for middle and high school students that develop students’ awareness of STEM degrees and careers and foster positive attitudes, confidence, and students’ ability to see themselves in STEM fields. Theories and methodologies from interactional ethnography guide our examination of ways Science Coach (SC) addresses these needs by educating and supporting 6th–12th-grade science teachers and their students as students identify and solve real problems through authentic research and invention. In this system-level study conducted alongside the program’s Chief Executive Officer (CEO), we document and analyze the actors, roles, and relationships to (re)present the SC use-inspired research and invention ecosystem. We also analyze student outcome data collected by the program to examine what is socially accomplished by the actors within the ecosystem. Six design principles guiding SC emerge from our analysis. The student outcomes we document emerge from data elements that SC has chosen to collect as indicators of their success. Analysis of student surveys showed that of the 12th-grade students matriculating from the program since 2019 (N = 612), a subset (n = 234) shared their college degree choice in the final questionnaire. Of these respondents, 91.5% (n = 214) reported that they were pursuing a STEM degree or career after participating in one or more years in SC. Among respondents who identified as underrepresented minorities (URM), 90.3% (n = 149) reported the same. With the growing need for STEM and STEM-related opportunities for all, learning and career readiness programs like SC serve as a potentially scalable model for bridging this gap.